Panduan Konseling Kelompok Behavioral Teknik Modeling untuk Meningkatkan Minat Kewirausahaan Mahasiswa - Eva Kartika Wulan Sari (Universitas PGRI Palembang, 2023)
This study aims to develop a group counseling guide for behavioral modeling techniques to increase student entrepreneurial interest because unemployment is the biggest problem faced nationally so the importance of Guidance and Counseling for students can be carried out in order to maximize entrepreneurial potential and minimize unemployment rate that is being faced by the nation. Indonesia prioritizes students from Alor Regency, East Nusa Tenggara Province. This type of development uses the ADDIE model which is still in the Develop stage or developing the design to become a finished product. The research instruments included a needs questionnaire, an interview guide, a student entrepreneurial interest scale, an assessment format for group counseling guidelines, and behavioral modeling techniques. There are three stages in assessing the validity and reliability of this behavioral modeling technique group counseling guide: testing the validity of Guidance and Counseling material experts, testing the validity of Guidance and Counseling media experts, and testing the validity of entrepreneurship experts. The expert validity assessment shows that the development of a guide to preparing students for entrepreneurship using group counseling behavioral modeling techniques shows that it is appropriate, functional, and easy to use.